2019
DOI: 10.1007/s11769-019-1065-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Metro Station Ridership Considering Spatial Heterogeneity

Abstract: This study aims to explore the role of spatial heterogeneity in ridership analysis and examine the relationship between built environment, station attributes and urban rapid transit ridership at the station level. Although spatial heterogeneity has been widely acknowledged in spatial data analysis, it has been rarely considered in travel behavior studies. Four models (three global models-ordinary least squares (OLS), spatial lag model (SLM), spatial error model (SEM) and one local model-geographically weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…For instance, using oneweek data for all stations in the Shenzhen metro and bus systems, Tu et al (2018) found that increased road density encourages a larger number of people to travel by bus and metro. Similar studies conducted by Zhao et al (2014) and Gan et al (2019b) also concluded that road density (or road length) is positively and significantly associated with urban rail transit station ridership. Durning and Townsend (2015) observed a positive relationship between rapid transit station ridership and intersection density based on data collected in Canada's five largest cities.…”
Section: Station Level Studiessupporting
confidence: 72%
See 2 more Smart Citations
“…For instance, using oneweek data for all stations in the Shenzhen metro and bus systems, Tu et al (2018) found that increased road density encourages a larger number of people to travel by bus and metro. Similar studies conducted by Zhao et al (2014) and Gan et al (2019b) also concluded that road density (or road length) is positively and significantly associated with urban rail transit station ridership. Durning and Townsend (2015) observed a positive relationship between rapid transit station ridership and intersection density based on data collected in Canada's five largest cities.…”
Section: Station Level Studiessupporting
confidence: 72%
“…Distance to city center, a measure of regional accessibility, has also been examined in the literature. In two empirical studies pertaining to Nanjing, China, the effects of distance to city center on metro station ridership have been found insignificant (Zhao et al, 2014;Gan et al, 2019b). However, based on the daily boardings data of light rail transit for the Baltimore Metro collected, Maryland, distance to city center was found to have a negative effect on ridership.…”
Section: Station Level Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Hu et al [17] used the generalized additive mixed effects model (GAMM) to investigate the nonlinear relationship between determinants and the attractiveness of car sharing. Since spatial autocorrelation is always observed when dealing with spatial data, spatial econometric models are usually used to deal with this issue [15,33,34]. Gan et al [33] applied the spatial error model and found the factors that significantly influence station-level ridership while controlling for spatial autocorrelation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This limitation is overcome by the spatial regression models, which have already been used for travel demand forecasting (Gan et al 2019;Lopes, Brondino and Rodrigues da Silva 2014;Sarlas and Axhausen 2016;Wang 2001). These models can consider the spatial autocorrelation by means of an explanatory variable, obtained from a spatially lagged dependent variable, or by the residual term of the model, and both of them include a spatial weight matrix normally based on the distance between the points of the database (Fotheringham et al 2003).…”
Section: Bulletin Ofmentioning
confidence: 99%